MODEL PENGEMBANGAN PEMBELAJARAN BOLABASKET MELALUI PERMAINAN LUMBA JARING BAGI SISWA KELAS VII SMP NEGERI 2 TALANG KABUPATEN TEGAL TAHUN 2015 - Mita Ayu Septiani; Endang Sri Hanani (Universitas Negeri Semarang, 2016)
The purpose of research to produce a basketball learning model with lumba jaring games at seventh grades students of SMPN 2 Talang Tegal Regency 2015 in the physical education learning. The methods of research is procedural development research, The data analysis technique used is deskriptif presentase. From the test results obtained expert evaluation of data are, experts of physical education 90.53% (good), expert's of learning I 90% (good), experts of learning II 88% (good), small group trial 84,95% (good), the field test 89.35% (good). from the data, it can be conclude learning model through lumba jaring games can be used for students of SMP Negeri 2 TalangTegal. Based on the result, lumba jaring games can be used in the process of sport learning.